RESOURCE-TARGET ASSESSMENT OF THE COMPANY’S ACTIVITIES EFFECTIVENESS - V. Busov (Вестник университета, 2019)
The need to assess the effectiveness of the use of resources from workplaces through the departments to the company as a whole has been substantiated. The main factors that form the level of use of incoming to the workplace and the structural elements of the system of initial resources has been identified. The role of this person as the main element of the workplace and the main factor of its efficiency has been shown. A significant place in the article is the disclosure of the structure of the system of relations in the company, their content and role in the effectiveness of its activities. An attempt to find indicators of the level of use of resources and methods of their calculation acceptable from the author’s point has been done. It has been proposed to use the company’s resources according to the processes of implementation of the company’s target functions within a certain period.